The Concept of Ulama and Umara in the Qanun Meukuta Alam: a Cultural Perspective (Jurnal Adabiya, 2025)
The pinnacle of Aceh’s political and cultural prosperity occurred during the reign of Sultan Iskandar Muda (1607–1636), who implemented structural reforms through the Qanun Meukuta Alam, a royal legal code regulating socio-cultural order, law, and governance. This Qanun reflects a synergy between Ulama and Umara, two key elements of Islamic leadership in Aceh. This study employs a descriptive qualitative method, with data collected through library research. To address the two main issues of this study namely, the nature of the relationship between Ulama and Umara within the Qanun Meukuta Alam and how the structure of the kingdom supported this relationship the study applies Talcott Parsons’ Structural Functionalism theory, focusing on the AGIL framework. The findings based on the AGIL analysis indicate that the adaptation process undertaken by Sultan Iskandar Muda as Umara involved incorporating Ulama as partners in governance and appointing the Panglima Polem as the holder of formative authority based on the counsel of the Ulama. The goal attainment pursued by the Umara was the implementation of laws grounded in Islamic law (sharia) in order to establish a prosperous society.AbstrakPuncak kejayaan Aceh terjadi pada masa pemerintahan Sultan Iskandar Muda (1607–1636), yang melakukan reformasi struktural melalui Qanun Meukuta Alam, sebuah undang-undang kerajaan yang mengatur tatanan sosial budaya, hukum, dan pemerintahan. Dalam Qanun ini tercermin sinergi antara Ulama dan Umara, dua elemen kunci dalam kepemimpinan Islam di Aceh. Metode yang digunakan dalam kajian ini adalah kualitatif deskriptif. Pengumpulan data dilakukan dengan telaah pustaka. Untuk menjawab dua permasalahan dalam kajian ini,yaitu bagaimana hubungan Ulama dan Umara dalam Qanun Meukuta Alam dan bagaimana struktur Kerajaan mendukung hubungan Ulama dan Umara digunakan teori teori Fungsionalisme Struktural Talcott Parsons dengan fokus kajian pada konsep AGIL. Hasil kajian dengan konsep AGIL terhadap Qanun Meukuta Alam menunjukkan bahwa proses adapatasi yang dilakukan oleh Iskandar Muda sebagai Umara adalah memasukkan Ulama sebagai mitra Umara dalam pemerintahan. Dan menetapkan Panglima Polem sebagai pemegang hak formatur yang berlandaskan nasehat ulama. Goal attainment yang dituju oleh Umara adalah menjalankan undang-undang yang berlandaskan syariat Islam untuk terciptanya masyarakat yang sejahtera.